POLYLACTIC ACID INTERACTIONS WITH BIOCERAMIC SURFACES - IRSAI, Izabella; BRÂNZANIC, Adrian M.V.; SILAGHI-DUMITRESCU, Radu (Studia Universitatis Babeș-Bolyai Chemia, 2021)
Molecular dynamics simulations were employed in order to analyze the interfacial interaction of polylactic acids with zirconia and hydroxyapatite surfaces. The interactions of polymers on five crystallographic planes were simulated. Silane coupling agents can improve the interactions between the bioceramic surfaces and the polylactic acids. The effects of the coupling agents are more evident in the presence of hydroxyapatite surfaces. Weak interactions hold together the polylactic acids and bioceramic systems. These interactions are formed between the hydrogen atoms from methyl groups or from the main chains of the polylactic acids and the oxygens of the surfaces. Polylactic acids change their conformations after molecular dynamics simulations due to the interactions. The conformation changes are more obvious when silane coupling agents are added to the polylactic acids and bioceramic systems.